Functional elements of entrusted professional activities for dental educators: protocol for a scoping review - Abu Bakar, Noraini; Roslan, Nurhanis Syazni; Haq, Muhammad Ainul; Mustafa Byrnes, Yasmin; Yusoff, Muhamad Saiful Bahri (JMIR Publications, 2025)
Background: Assessing the competencies of health profession educators presents significant challenges, leading to the suggestion of implementing Entrustable Professional Activities (EPAs) as a potential solution. EPAs refer to the authority granted to individuals to perform tasks with a specified level of trust and competence. The concept of EPAs emerged from the complexities of competency-based medical education. This scoping review highlights the emerging yet underdeveloped field of EPAs for dental educators. Despite their established utility in medical education, the concept remains relatively novel for dental educators, with limited literature and inconsistent application across studies. Objective: This paper presents a scoping review protocol aimed at systematically elucidating the extent, range, and nature of the literature on EPAs for dental educators, as evaluated in the included resources. This review seeks to answer the following research question: what are the key functional elements of EPAs for dental educators as described in the existing literature? Methods: This scoping review will be conducted in accordance with the framework outlined by Arksey and O’Malley, enhanced by the Joanna Briggs Institute (JBI) guidelines. The literature search will use a 3-step strategy across 5 electronic databases (PubMed, Google Scholar, Scopus, Cochrane Library, and ProQuest), along with additional screening of gray literature. Primary data from relevant studies published from the introduction of EPAs in 2005 through 2024 will be analyzed. This review will include peer-reviewed literature focused on EPAs, specifically those involving dental educators in undergraduate, postgraduate, or continuing education contexts. Studies of any design (qualitative, quantitative, or mixed methods), as well as conceptual papers and reviews, will be considered. Only English-language studies will be included. The literature search process will involve a librarian, while study selection and evidence charting will be conducted by 4 independent reviewers. These reviewers will independently screen titles, abstracts, and full texts against the inclusion criteria. Data will be charted using a standardized extraction form and analyzed thematically. Results: Findings will be presented in both tabular and narrative formats, highlighting the range, characteristics, and key components of EPAs relevant to dental educators. In addition, these findings will be mapped to the competencies of dental educators. This review is estimated to be completed within 6 months and aims to identify gaps for future research, ultimately supporting the advancement of competency-based dental education. The results of this review will serve as a foundation for a larger study focused on developing a framework of EPAs specifically tailored for dental educators.